Identity Discovery and Verification in Artist-Entrepreneurs: An Active Learning Exercise. (3rd April 2017) - Bass, A. Erin
ABSTRACT: Entrepreneurship curricula are becoming increasingly more interdisciplinary, with higher education institutions offering a variety of "entrepreneurship and" courses that cross the boundaries into other fields. Despite this, many entrepreneurship curricula are centered on business theory, which is not suitable for nonbusiness students. For example, business students are trained to define success by financial statements and organizational viability, whereas artists enjoy success by achieving creative satisfaction. This article explores the importance of identity to the entrepreneurial process, highlighting the similarities and differences between the artist and entrepreneur identities. Pedagogical in approach, the article demonstrates the utility of an active learning exercise in identity discovery and verification for artist-entrepreneurs. It highlights the critical role of identity for artist-entrepreneurs, the need to develop curricula for nonbusiness students to maximize learning, and the utility of this exercise as a starting point for artist-entrepreneurs to enact the entrepreneurial mind set in their creative work.